AN EXAMINATION OF INVESTOR BEHAVIOR AND INVESTMENT PORTFOLIO TRENDS IN KRISHNAGIRI DISTRICT - Bhuvaneswari, M.; Venkatesh, R. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The main goal of this study is to look into how middle-class entrepreneurs invest in Krishnagiri district. This topic is important because the middle class in our country gets a lot of attention from policymakers & researchers due to its potential for growth. We want to answer some key questions about how these individuals invest and if their savings are increasing. Also, we’ll consider how their age affects their investment choices. So, this paper aims to find out how different ages and income levels influence investment preferences among middle-income earners in Krishnagiri district.